Pembentukan Struktur Fukubun (複文) Kausalitas pada Pertuturan Pemelajar Bahasa Jepang: Kajian Generatif Transformasional - Mintarsih Mintarsih; Bambang Yulianto; Subandi (Undiksha Press, 2022)
This study aims to analyze how the beginner Japanese language learner builds the fukubun constructions. The analysis is focused on the conjunction of causality with the core clause predicated as a transitive verb. The subjects of this study were 62 Japanese language students. The procedure for analyzing research data was done by means of interview transcription, reduction and coding. Data analysis uses transformational generative grammar, namely: analysis of phrase structure-rules, lexicon rules, and transformation rules. This study shows: (1) 3 structures of fukubun namely AB type, BB type, and BB (2) type; (2) causal conjunctions in the speech of the research subjects are: -kara, -node, -tame ni, -desukara/dakara, -te/de; (3) the transformation process on the data, namely: addition, deletion, permutation, substitution, and verb modification.